Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament Terhadapjpemahaman Konsep Matematis Peserta Didik Kelas VIII SMPN 3 Batusangkar - SANTI SASTIKA SELI (Departemen Matematika, 2019)
One of the purpose in mathematics learning is understanding of mathematical concepts. It is the most important in mathematics learning because it is the main thing that must be mastered in the learning mathematics. In fact, understanding of mathematical concepts of students at class VIII SMPN 3 Batusangkar still low. One of the effort that can be used to solve this problem is by applying cooperative learning model Teams Games Tournament type. Type of the research is a quasi experiment design with Static Gropu Design. The sample of this research were class VIII.3 and VIII.4. Instrument used was test in essay form. Result of research show that understanding of mathematis concepts of students using cooperative learning model teams games tournament type better than understanding of mathematis concepts of students using direct learning. Keywords - Understanding of Mathematical Concepts, Teams Games Tournament, Direct learning